A review on the clinical pharmacokinetics of hydralazine. (3rd October 2022) - Shahzad Qamar, Asma; Zamir, Ammara; Khalid, Sundus; Ashraf, Waseem; Imran, Imran; Hussain, Iltaf; Rehman, Anees Ur; Saeed, Hamid; Majeed, Abdul; Alqahtani, Faleh; Rasool, Muhammad Fawad
ABSTRACT: Introduction: Hydralazine is a vasodilator used to treat hypertension, pre-eclampsia, and heart failure. The current article reviews the clinical pharmacokinetics (PK) of hydralazine, which can be useful for clinicians in optimizing its dose and dosing frequency to avoid adverse effects and unexpected interactions that could risk patients' lives. Areas covered: This review has summarized the PK parameters for hydralazine after performing an extensive literature search. It includes 20 publications that were selected after applying eligibility criteria out of a pool of literature that was searched using Google Scholar, PubMed, Cochrane Central, and EBSCO databases. The included studies consisted of concentration vs. time profiles of hydralazine. If the PK data were not tabulated in the given study, the concentration vs. time profiles were scanned for the extraction of the PK data. The PK parameters were calculated by applying a non-compartmental analysis (NCA). Expert Opinion: The current review will aid clinicians in understanding hydralazine PK in different disease populations. This clinical PK data might also be helpful in the development of a pharmacokinetic model of hydralazine.